2013
DOI: 10.1371/journal.pone.0070968
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Immunoregulatory Effects of Culture-Expanded Mesenchymal Stromal Cells and CD4+25+Foxp3+ Regulatory T Cells on Skin Allograft Rejection

Abstract: Mesenchymal stromal cells (MSCs) are seen as an ideal source of cells to induce graft acceptance; however, some reports have shown that MSCs can be immunogenic rather than immunosuppressive. We speculate that the immunomodulatory effects of regulatory T cells (Tregs) can aid the maintenance of immunoregulatory functions of MSCs, and that a combinatorial approach to cell therapy can have synergistic immunomodulatory effects on allograft rejection. After preconditioning with Fludarabine, followed by total body i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The upregulation of IL-10 and TGF-β is important for the differentiation and proliferation of Tregs. Tregs have very important immunoregulatory effects and play a significant role in the induction of immunotolerance or the maintenance of immunosuppressive activity (44). These data provide evidence that increased allograft survival following ADSCs OX40Ig administration, at least in part, occurs in association with the increased intragraft expression of genes associated with altered T cell differentiation, as well as a shift from a pro-inflammatory to an anti-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of IL-10 and TGF-β is important for the differentiation and proliferation of Tregs. Tregs have very important immunoregulatory effects and play a significant role in the induction of immunotolerance or the maintenance of immunosuppressive activity (44). These data provide evidence that increased allograft survival following ADSCs OX40Ig administration, at least in part, occurs in association with the increased intragraft expression of genes associated with altered T cell differentiation, as well as a shift from a pro-inflammatory to an anti-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…In our group, we implemented the use of a combined cell therapy approach for the treatment of acute GVHD [53], induction of mixed chimerism following BMT [54], and prevention of allogeneic skin-graft rejection [55]. We observed that the combined cell therapy groups in all models showed enhanced survival and reduced clinicopathological symptoms.…”
Section: Combined Cell-based Immune Modulationmentioning
confidence: 99%
“…These data suggest that the combination of MDSCs and Tregs has potent immunoregulatory effects in mice and humans. Previous reports suggest that the combination of MSCs and Treg cell therapy have enhanced therapeutic e cacy in transplantation model [43][44][45]. However, the mechanism underlying cross talk between MSC and Treg remains unclear [46].…”
Section: Discussionmentioning
confidence: 99%